Efficacy of a Novel Optimized Pulsed Light Source (MaxG) for the Treatment of Facial Vascular Lesions - SAÇAK, BÜLENT (MARY ANN LIEBERT, INC, 2017)
Background and objective: Facial vascular malformations can cause a number of functional problems, including difficulties in breathing, eating, speech, and mobility. Psychological problems can also arise due to the possible unpleasant appearance of such lesions. Further, these lesions can lead to a number of complications, including pain, ulceration, infection, and significant bleeding. Many treatments have been proposed in the literature. Laser therapy (and its related treatments by non-coherent light sources) is now considered the gold standard in the treatment of the majority of vascular lesions. Methods: Here, we present our experience with a novel optimized pulsed light source for the treatment of vascular anomalies. In this prospective study, we evaluate the clinical outcomes of 30 patients treated with this method. Results: Our results confirm the efficacy and safety of this treatment for facial vascular lesions. Conclusions: Based on our experience and results, we believe this device could be considered as both an alternative monotherapy and a useful adjunctive to the already existing laser instruments.
Keywords: vascular malformation; angioma; intense pulsed light; MaxG; facial vascular lesion; laser; PORT-WINE STAINS; DYE-LASER TREATMENT; SKIN-LESIONS; PHOTOTHERMOLYSIS; MALFORMATIONS; HEMANGIOMAS; NEODYMIUM; THERAPY